O fazer criativo presente no processo de produção de ilustradores e designers - Freire, Renan Cardoso de Luna (2020)
This dissertation addresses the productive processes of creative professionals in order to identify possible common trait between their work and reveal essential conscious and intuitive elements that run through their visual constructions. During the interview of eight professionals working in Rio de Janeiro using the deep interview method, it was possible to realize that artistic activities are inexhaustible sources for creativity, and that the creative and productive process, when well understood and conscious, generates productivity and contributes to economic development. With a focus on the creative process that each professional establishes, whether in the area of illustration, design or visual arts, it was possible to identify the individuality that each creative needed to achieve in order to obtain specific results and leverage production processes. Transversal to research, as a result, comic strips were developed, materializing through art itself, the questioning between intuitive and artistic creative making